Implementasi Parate Eksekusi Sebagai Penyelesaian Kredit Bermasalah Pada Bank - Pratiwi, Widya Sari; Mahmudah, Siti (PAMALI: Pattimura Magister Law Review, 2024)
Introduction: The occurrence of credit problems can result in huge losses that need to be addressed. One attempt to rescue troubled credit is to carry out a parate execution, that is to say, attempting to save trouble credit without the involvement of a court.Purposes of the Research: The study aims to examine the application of parate execution as an attempt to settle troubled credit in banks. In practice, there is a challenge that banks have to face, namely bad credit.Methods of the Research: This study uses a method of normative law research with a statue approach and a conceptual approach. (conceptual approach). The legal material consists of primary legal material namely regulations of laws, and secondary legal materials namely books, journals and official websites collected using library study techniques. Research objects refer to problematic credits as topics studied in research and analysis used using qualitative analysis techniques.Results of the Research: The results of the research show that the implementation of the parate of execution is realized by the execution of the right of dependency as regulated in Article 6 of the Act on the Right of Dependency. Execution is done through auction execution. A previously agreed object will be auctioned if there is a failure to perform. However, in practice also found obstacles such as the low level of fans or buyers, lawsuits and objections from the debtor, as well as KPKNL who have no authority in carrying out the execution of the object of security so that can not deal with the problem of debtor who makes the opposition and refuses to hand over the item of security that has been auctioned.